Reduction-Induced Synthesis of Reduced Graphene Oxide-Wrapped Cu2O/Cu Nanoparticles for Photodegradation of Methylene Blu - Kalubowila, K. D. R. N.; Gunewardene, M.Siyath; Dissanayake, Dhammike; Jayathilaka, Charith; Jayasundara, J.M.Dilushan; Jayasingha, Lakmini Kaushalya; Gao, Yun; Jayanetti, J. K. D. S. (ACS Publications, 2021)
A photocatalytic composite in powder form having nanosized Cu2O/Cu granules wrapped in multilayered reduced graphene oxide (rGO) sheets was synthesized. The fabrication process was initiated by potentiostatic electrodeposition of n-type Cu2O thin films on Ti substrates in an acetate bath. Peeled-off Cu2O thin films were next subjected to ultrasonic mixing with graphene oxide (GO) by maintaining a Cu2O/GO mass ratio of 125:10. Chemical reduction using ascorbic acid converted Cu2O partially to Cu, while converting GO completely to rGO as confirmed by Fourier transform infrared spectroscopy (FTIR), X ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD). Transmission electron microscopy (TEM) images of the composite confirmed the presence of Cu nanoparticles of the size of tens of nanometers within the photocatalyst, Cu2O. The fabrication process therefore implicitly favors synthesis of nanosized Cu playing the role of a co-catalyst. The Cu2O/Cu/rGO composite showed significantly higher ability to degrade methylene blue in solution, while the effects due to photocorrosion were minimal during a month of testing when compared with Cu2O alone. The layered rGO provides an effective medium for transporting photoelectrons to the reactant while inhibiting photocorrosion. Furthermore, the composite demonstrated its ability to split water under visible light in the presence of methanol and creates a promising platform to further develop a variety of other photocatalytic applications.
Keywords: photocatalyst; cuprous oxide; co-catalyst; nanocomposite; reduced graphene oxide